Global Landscape of Retracted Publications in Data Science: A Bibliometric Analysis (1993-2025) - Madhu, S; Ashwini Kumar, R; Siddiq, Aboobakar; Chaman Sab, M (Information Research Communications, 2026)
Background/Aim This bibliometric study aims to present a global analysis of 5,398 retracted publications in Data Science from 1993 to 2025 using data from Retraction Watch, analysed with Microsoft Excel. Methodology The study examines temporal trends, retraction delays, document types, nature of retraction, subject associations, counrty-wise production, and publisher and journals contributions. Results Retractions were rare before 2015 but increased sharply after 2019, peaking in 2022 with 2,705 cases (50.11%). Most publications were retracted within one to two years (2,306; 42.72%). Technology (2,787) and Computer Science (2,215) were the most frequent co-associated subjects. China (3,902), India (962), and Saudi Arabia (304) accounted for the highest number of retractions. Hindawi (3,043) and IOS Press (1,161) were the leading publishers, research articles dominated document types (94.79%), and full retractions accounted for 98.72% of cases. Conclusion The findings indicate that retractions in Data Science are a recent and global phenomenon, reflecting increased research output and strengthened editorial oversight.
Keywords: Bibliometrics; Data Science; Research Integrity; Retracted Publication; Retraction Watch; Scientific Misconduct.